Minimal Window Duration for Accurate HRV Recording in Athletes - Bourdillon, Nicolas; Schmitt, Laurent; Yazdani, Sasan; Vesin, Jean-Marc; Millet, Grégoire P. (Frontiers in Neuroscience, 2017)
Heart rate variability (HRV) is non-invasive and commonly used for monitoring responses to training loads, fitness or overreaching in athletes. Yet, the recording duration for a series of RR-intervals varies from 1 to 15 min in the literature. The aim of the present work was to assess the minimum record duration to obtain reliable HRV results. RR-intervals from 159 orthostatic tests (7min supine, SU, followed by 6 min standing, ST) were analyzed. Reference windows were 4 min in SU (min 3 to 7) and 4 min in ST (min 9 to 13). Those windows were subsequently divided and the analyses were repeated on eight different fractioned windows: the first min (0-1), the second min (1-2) the third min (2-3), the fourth min (3-4), the first two min (0-2), the last two min (2-4), the first three min (0-3) and the last three min (1-4). Correlation and Bland & Altman statistical analyses were systematically performed. The analysis window could be shortened to 0-2 instead of 0-4 for RMSSD only, whereas the 4-min window was necessary for LF and total power. Since there is a need for 1 min of baseline to obtain a steady signal prior the analysis window, we conclude that studies relying on RMSSD may shorten the windows to 3 min (= 1+2) in SU or seated position only and to 6 min (=1+2 min SU plus 1+2 min ST) if there is an orthostatic test. Studies relying on time- and frequency-domain parameters need a minimum of 5 min (=1+4) min SU or seated position only but require 10 min (=1+4 min SU plus 1+4 min ST) for the orthostatic test.